The Efficacy of a Task-Orientated Group-Intervention Programme for Children with Specific Learning Disorder with Co-morbid Developmental Coordination Disorder - Crafford, Roche (Department of Health and Rehabilitation Sciences, 2019)
Background: Specific Learning Disorder (SLD) is described as a neurodevelopmental disorder affecting academic performance and/or activities of daily life including reading, writing or calculation skills during formal years of schooling. There is strong evidence that Developmental Coordination Disorder (DCD), presenting as a disorder affecting motor skills, may be co-morbid with other neurodevelopmental conditions, including SLD. Children with SLD and co-morbid DCD (SLD/DCD) are considered a unique group. Learners with SLD/DCD experience a significant, negative impact on daily tasks such as selfcare, play, leisure and schoolwork. Neuromotor Task Training (NTT), a form of intervention, has been reported to be effective in reducing the activity limitations in children with DCD. However, information regarding the most effective treatment to improve function and behaviour in learners with SLD/DCD, who attend special schools, has not yet been investigated. The aim of this study was to evaluate the efficacy of task-orientated NTT group intervention programme on motor performance, behavioural profile and health related quality of life (HRQOL) of children with SLD/DCD attending a School for Learners with Special Education Needs (LSEN) in Cape Town, South Africa. Method: A quantitative, quasi-experimental design with pre- and post-tests was used. Learners were included if they presented with a primary or secondary diagnosis of SLD plus DCD (scoring at or below the 16th percentile on the Motor Assessment Battery for Children 2nd Edition (MABC-2) and a functional motor problem, as identified by the MABC checklist), aged between 6–10 years and grade 1-4. Learners were allocated to either NTT (n = 18) or Usual Care (n = 18) groups. The Usual Care (UC) group continued with normal activity, but did not receive physiotherapy. The MABC-2, parent and teacher Strengths and Difficulties Questionnaire (SDQ) and self-reported European Quality of Life 5- Dimensions questionnaire for Youth (EQ-5D-Y) were used to assess performance pre- and post - intervention. The NTT program was implemented for nine weeks, with two 45-60 minute sessions per week. Results: There was a significant difference in Total Standard Score (TSS) between NTT and UC groups (p=0.048). In the NTT group, the mean TSS (p < 0.001) and Balance score (p= 0.02) significantly improved over the intervention period. The control group did not show any significant changes over the intervention period while receiving UC. The intervention group did not show any significant changes in Behavioural Profile (SDQ) over the intervention period while receiving NTT, according to v teachers. The results indicate that the intervention group showed a significant change in Behavioural Profile (SDQ) in the Behaviour/Conduct domain (p=0.01) over the intervention period while receiving NTT, according to parents. There was no significant change in HRQOL according to the self-report EQ-5D-Y. Conclusion: The results of this study showed that a task orientated programme (NTT), presented in small groups, has a positive effect on motor performance in learners SLD/DCD.